Limbus-centered marking technique-assisted continuous circular capsulorhexis. Issue 2 (15th January 2021) - Wang, Xiaogang; Dong, Jing; Deng, Minghui
Abstract : Abstract: To introduce a limbus-centered continuous circular capsulorhexis (CCC) marking technique. Compared with traditional capsulotomy diameter mark technique, a self-designed limbus-centered capsulotomy mark (LCM) was used to perform the routine cataract surgery in this observational study. Ten eyes were included in each group. The area outer/inner 5.5-mm CCC ring, the furthest/nearest distance from the capsule margin to the intraocular lens (IOL) margin, the CCC total coverage IOL area were measured and compared between this 2 groups. No significant differences were found for all the comparison parameters between the 2 groups (all P  > .05). However, the capsule total coverage area, area inner 5.5-mm ring was lower in the LCM group, which demonstrated advantage of LCM. The limbus-centered capsulotomy diameter mark, as an inexpensive and convenient method, helps to perform limbus-centered capsulorhexis with not only a 360° overlapping capsular edge but also well-centered IOL optics. Abstract : Supplemental Digital Content is available in the text